Monitoring dan Analisis QoS Jaringan Wireless LAN di Gedung Harni Koesno: Studi Kasus dengan Wireshark dan Thiphone - slamet purwo santosa; ahmad tajuddin (Teknik Elektro Universtias Krisnadwipayana, 2026)
This study examines the quality of the Wireless LAN (WLAN) network at Harni Koesno Building, Department of Midwifery, Poltekkes Kemenkes Jakarta III, focusing on Quality of Service (QoS) analysis. The aim is to measure and evaluate WLAN QoS performance through aspects such as delay, bandwidth, jitter, and packet loss. Data collection techniques included direct observation, network analysis software and user surveys. The results show a delay of 22.22 ms, 0% packet loss, and 68.70 ms jitter, all categorized as